(untitled) (International Journal of Engineering and Computer Science, 2017)
A number of scripting languages are available today. Based on the characteristics and features they have, their usage is defined. Usage of scripting languages in the field of data mining and other research areas is increasing as they are simple, powerful and more importantly they are open source. This paper discusses about a few scripting languages and their applications in data mining. We have used one of the scripting languages i.e. Python and demonstrated how it is useful for the research.